2016
DOI: 10.3389/fnins.2016.00211
|View full text |Cite
|
Sign up to set email alerts
|

Developing Brain Vital Signs: Initial Framework for Monitoring Brain Function Changes Over Time

Abstract: Clinical assessment of brain function relies heavily on indirect behavior-based tests. Unfortunately, behavior-based assessments are subjective and therefore susceptible to several confounding factors. Event-related brain potentials (ERPs), derived from electroencephalography (EEG), are often used to provide objective, physiological measures of brain function. Historically, ERPs have been characterized extensively within research settings, with limited but growing clinical applications. Over the past 20 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 35 publications
4
76
0
Order By: Relevance
“…A recent study in our group also demonstrated these temporal and spectral characteristics using magnetoencephalography (MEG), further validating the existence of BRO effects across different modalities (Liu, Ghosh Hajra, Cheung, Song, & D'Arcy, 2017). Moreover, studies have also pointed to the potential utility of the BRO response in clinical brain function assessments (Bonfiglio et al, 2013(Bonfiglio et al, , 2014, with further possibility of deployment in bedside evaluations (Ghosh Hajra et al, 2016.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…A recent study in our group also demonstrated these temporal and spectral characteristics using magnetoencephalography (MEG), further validating the existence of BRO effects across different modalities (Liu, Ghosh Hajra, Cheung, Song, & D'Arcy, 2017). Moreover, studies have also pointed to the potential utility of the BRO response in clinical brain function assessments (Bonfiglio et al, 2013(Bonfiglio et al, , 2014, with further possibility of deployment in bedside evaluations (Ghosh Hajra et al, 2016.…”
supporting
confidence: 56%
“…The BRO response has mainly been described under resting conditions with or without passive fixation, and is particularly prominent in the delta frequency range (0.5-4 Hz). Moreover, studies have also pointed to the potential utility of the BRO response in clinical brain function assessments (Bonfiglio et al, 2013(Bonfiglio et al, , 2014, with further possibility of deployment in bedside evaluations (Ghosh Hajra et al, 2016. A recent study in our group also demonstrated these temporal and spectral characteristics using magnetoencephalography (MEG), further validating the existence of BRO effects across different modalities (Liu, Ghosh Hajra, Cheung, Song, & D'Arcy, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…As introduced elsewhere [ 37 ], the rapid assessment framework utilizes a compressed auditory stimulus sequence with interlaced tones and words to elicit brain responses across four different functional domains—auditory sensation (N100 ERP), attention (P300 ERP), and semantic language (N400 ERP)—in approximately 5 min (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated the successful evaluation of the N400 response in 100 healthy individuals using a point-of-care enabled device [ 34 ], then employed this device to track the progress of rehabilitation therapy in a brain-injured patient [ 6 ]. More recently, we demonstrated a rapid evaluation platform known as the ‘brain vital sign’ framework [ 37 ], which enables the rapid assessment of several brain function indicators including the N400 (semantic language), N100 (sensory processing) [ 38 ] and P300 (attention orienting) [ 39 ]. The brain vital sign framework employs a portable, low-density EEG system, with automated, user-friendly software for easy clinical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation